2008 International Conference on Electronic Design 2008
DOI: 10.1109/iced.2008.4786632
|View full text |Cite
|
Sign up to set email alerts
|

Normalized Least Mean Square adaptive noise cancellation filtering for speaker verification in noisy environments

Abstract: In this paper, we present a speaker verification system based on the Hidden Markov Models (HMMs) and Normalized Least MeanSquare (NLMS) adaptive filtering. The aim of using NLMS adaptive filtering is to improve the HMMs performance in noisy environments. A Malay spoken digit database is used for the testing and validation modules. It is shown that, in a clean environment a Total Success Rate (TSR) of 89.97% is achieved using HMMs. For speaker verification, the true speaker rejection rate is 25.3% while the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…This section shows the computational complexity when normalised least mean squares filter (NLMS) and recursive least squares filter (RLS) are used (Ilyas et al 2008;Cioffi and Kailath 1984;Dhiman et al 2013). These parameters will serve in the simulations carried out in the following section.…”
Section: Computational Complexity and Convergence Speedmentioning
confidence: 99%
See 1 more Smart Citation
“…This section shows the computational complexity when normalised least mean squares filter (NLMS) and recursive least squares filter (RLS) are used (Ilyas et al 2008;Cioffi and Kailath 1984;Dhiman et al 2013). These parameters will serve in the simulations carried out in the following section.…”
Section: Computational Complexity and Convergence Speedmentioning
confidence: 99%
“…Li et al (2008) suggested an element space partially adaptive array in which each sub-array uses the delay-and-sum (DAS) weights (Saff and Kuijlaars 1997). The convergence speed is enhanced in comparison to fully adaptive array and noise power is increased mildly (Ilyas et al 2008;Cioffi and Kailath 1984;Dhiman et al 2013).…”
Section: Introductionmentioning
confidence: 96%
“…The process of detecting the presence of speech/non-speech is not a fully resolved problem in speech processing systems. Numerous applications such as robust speech recognition [ 11 , 12 ], real-time speech transmission on the Internet [ 13 ], noise reduction and echo cancellation schemes in telecommunication systems are affected by such a process [ 14 , 15 ]. The detection of speech/non-speech is not an easy task as it may look.…”
Section: A Review Of Voice Activity Detection Techniquesmentioning
confidence: 99%
“…In the above equation, w stands for the output of the algorithm, n stands for iteration number, μ is a adaptation constant which controls the rate of convergence, e is the error signal and y is the reference signal. In [83], normalized LMS algorithm was used for adaptive noise cancellation and performance gain of 21% was reported at 10 dB SNR for text-dependent speaker verification.…”
Section: Speaker Verification In Environmental Noisementioning
confidence: 99%